Becoming Dad: Expectant Fathers' Attachment Style and Prenatal Representations of the Unborn Child - Hedvig Svendsrud; Eivor Fredriksen; Vibeke Moe; Lars Smith; Stella Tsotsi; Anne Karin Ullebø; Gro Vatne Brean; Anne Kaasen; Mona Bekkhus (MDPI AG, 2023)
How expectant fathers think and feel about the unborn child (prenatal representations), has shown associations with fathers' postnatal parenting behaviors, observed father-infant interactional quality and child cognitive development. There is limited knowledge about fathers' prenatal representations. The present study examined if fathers' partner-related attachment styles were related to their prenatal representations of the unborn child. In the "Little in Norway Study", an ongoing prospective, longitudinal population-based study, 396 expectant fathers completed the Experiences in Close Relationships Scale at enrollment (mean gestational week = 23.76, SD = 4.93), and in gestational weeks 27-35 completed three questions assessing prenatal representations. Correlations of attachment style and prenatal representations were reported using logistic regression analyses. We found that an avoidant attachment style by fathers were predicted to have absent or negative representations on all three items (1) "strongest feeling about the unborn child" (Cl = 1.19-2.73), (2) "thoughts about child personality" (Cl = 1.16-1.87), and (3) "experiences of relationship with the child" (Cl = 1.14-1.75). Father anxious attachment style was not significantly associated with absent or negative prenatal representations. Results suggest that expectant fathers with a partner related avoidant attachment style have an increased risk of having absent or negative prenatal representations of the unborn child.